Caracterização biométrica, germinação e uso da técnica Biospeckle como ferrramenta auxiliar na determinação da viabilidade de sementes de Araçá-boi - Silva, Marcela Liege da (2016)
The Amazon has countless species with great economic potential, among these, the fruit has been highlighted by the generation of income and food for the population. These species are poorly studied, present as biggest obstacle, the lack of knowledge of its spread, such as the araca-boi (Eugenia stipitata), whose main problem refers to the dormancy of its seeds. The objective of the present work is performing a biometric characterization, germination and study of conventional and modern techniques to overcome dormancy of guava-ox. To this end, three experiments were performed: 1 – Biometric characterization, water absorption curve and vigor on araca-boi seeds; 2 – Osmopriming in araca-boi seeds germination and 3 – Biospeckle as tool auxiliary indetermining the viability araca-boi seeds. It was found that the plant population, from Manaus-AM, produced small, medium and large seeds, which showed 70.2%, 68.2% and 47.5% moisture. Increment greater water by the seed, occurred within one hour of absorption, regardless of size, and speed of water absorption was not influenced by its size. The imbibition curves, characterized the period of 144 hours, regardless of seed size, showed two physiological stages. The large and medium seeds showed lower values of conductivity, highest germination, because they have higher levels of force. Noted 100% of seeds germinated when primed in KNO3 for 12 hours, until 70 days of culture. The use of the technique of biospeckle was efficient in determining the viability and vigor of seeds of araca-boi. The large and medium seeds showed higher activities. The germination of large and medium seeds and seedling development correlated with the activity observed by the technique of biospeckle.